Sulfidation of Iron-Based Materials: A Review of Processes and Implications for Water Treatment and Remediation - Fan, Dimin; Lan, Ying; Tratnyek, Paul G; Johnson, Richard L; Filip, Jan; O'Carroll, Denis M; Nunez Garcia, Ariel; Agrawal, Abinash (Environmental science & technology, 2017)
Iron-based materials used in water treatment and groundwater remediation-especially micro- and nanosized zerovalent iron (nZVI)-can be more effective when modified with lower-valent forms of sulfur (i.e., "sulfidated"). Controlled sulfidation for this purpose (using sulfide, dithionite, etc.) is the main topic of this review, but insights are derived by comparison with related and comparatively well-characterized processes such as corrosion of iron in sulfidic waters and abiotic natural attenuation by iron sulfide minerals. Material characterization shows that varying sulfidation protocols (e.g., concerted or sequential) and key operational variables (e.g., S/Fe ratio and sulfidation duration) result in materials with structures and morphologies ranging from core-shell to multiphase. A meta-analysis of available kinetic data for dechlorination under anoxic conditions, shows that sulfidation usually increases dechlorination rates, and simultaneously hydrogen production is suppressed. Therefore, sulfidation can greatly improve the efficiency of utilization of reducing equivalents for contaminant removal. This benefit is most likely due to inhibited corrosion as a result of sulfidation. Sulfidation may also favor desirable pathways of contaminant removal, such as (i) dechlorination by reductive elimination rather than hydrogenolysis and (ii) sequestration of metals as sulfides that could be resistant to reoxidation. Under oxic conditions, sulfidation is shown to enhance heterogeneous catalytic oxidation of contaminants. These net effects of sulfidation on contaminant removal by iron-based materials may substantially improve their practical utility for water treatment and remediation of contaminated groundwater.
Keywords: Halogenation; podzemní voda; Sulfides; čištění vody; sulfidy; Water Purification; chemické látky znečišťující vodu; Groundwater; Iron; halogenace; Water Pollutants, Chemical; železo